Characterization of a novel plasmid type and various genetic contexts of bla OXA-58 in Acinetobacter spp. from multiple cities in China. - Yiqi Fu; Jingjin Jiang; Hua Zhou; Yan Jiang; Ying Fu; Yunsong Yu; Jianying Zhou (PLoS ONE, 2014)
BACKGROUND/OBJECTIVE: Several studies have described the epidemiological distribution of blaOXA-58-harboring Acinetobacter baumannii in China. However, there is limited data concerning the replicon types of blaOXA-58-carrying plasmids and the genetic context surrounding blaOXA-58 in Acinetobacter spp. in China. METHODOLOGY/PRINCIPAL FINDINGS: Twelve non-duplicated blaOXA-58-harboring Acinetobacter spp. isolates were collected from six hospitals in five different cities between 2005 and 2010. The molecular epidemiology of the isolates was carried out using PFGE and multilocus sequence typing. Carbapenemase-encoding genes and plasmid replicase genes were identified by PCR. The genetic location of blaOXA-58 was analyzed using S1-nuclease method. Plasmid conjugation and electrotransformation were performed to evaluate the transferability of blaOXA-58-harboring plasmids. The genetic structure surrounding blaOXA-58 was determined by cloning experiments. The twelve isolates included two Acinetobacter pittii isolates (belong to one pulsotype), three Acinetobacter nosocomialis isolates (belong to two pulsotypes) and seven Acinetobacter baumannii isolates (belong to two pulsotypes/sequence types). A. baumannii ST91 was found to be a potential multidrug resistant risk clone carrying both blaOXA-58 and blaOXA-23. blaOXA-58 located on plasmids varied from ca. 52 kb to ca. 143 kb. All plasmids can be electrotransformed to A. baumannii recipient, but were untypeable by the current replicon typing scheme. A novel plasmid replicase named repAci10 was identified in blaOXA-58-harboring plasmids of two A. pittii isolates, three A. nosocomialis isolates and two A. baumannii isolates. Four kinds of genetic contexts of blaOXA-58 were identified. The transformants of plasmids with structure of IS6 family insertion sequence (ISOur1, IS1008 or IS15)-ΔISAba3-like element-blaOXA-58 displayed carbapenem nonsusceptible, while others with structure of intact ISAba3-like element-blaOXA-58 were carbapenem susceptible. CONCLUSION: The study revealed the unique features of blaOXA-58-carrying plasmids in Acinetobacter spp. in China, which were different from that of Acinetobacter spp. found in European countries. The diversity of the genetic contexts of blaOXA-58 contributed to various antibiotics resistance profiles.